Effect of glycosylated hemoglobin protein molecule in treating diabetes - Qian, Kuo; Dong, Haiying; Qian, Jiayi; Gong, Jian (Cellular and Molecular Biology, 2020)
The object of this study was to observe and analyze the effect of glycosylated hemoglobin in treating diabetes and provide valuable guidance for clinical treatment. For this purpose, 160 patients treated in our hospital who were definitely diagnosed with diabetes after relevant examinations were classified into the study group. 160 cases with healthy physical examinations for the same period were enrolled as a reference group. Fasting blood glucose and glycosylated hemoglobin levels were measured in both groups, and inter-group comparisons were made. The detection results showed that the study group had significantly higher fasting blood glucose and glycosylated hemoglobin levels than the healthy reference group. The difference was statistically significant (p<0.05). Diabetic patients in the study group were also observed. The results showed that patients with complications had significantly higher fasting blood glucose and glycosylated hemoglobin levels than those without complications. Statistical significance existed, p<0.05. For diabetic patients, glycosylated hemoglobin detection is of great significance in profoundly affecting diabetes diagnosis and treatment and providing positive guidance, which means great value for evaluating disease control effects.